Fuzzy fixed point theorems on the complete fuzzy spaces under supremum metric - Suthep Suantai (2018)
© 2015, Suantai et al. By using the concept of a class of functions, the R$\mathcal {R}$-functions, we provide some fuzzy fixed point theorems on a space of fuzzy sets equipped with the supremum metric. By presenting a technique of constructing a sequence of successive approximations, we obtain some interesting results that improve many existing results. The related cases are also shown and discussed.